Pengaruh Stres Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Sinwa Makmur Perkasa Pratama - Novia Ardhana; Sugeng Suroso; Ery Teguh Prasetyo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine whether there is an effect of Job Stress and Job Satisfaction on Employee Performance at PT Sinwa Makmur Perkasa Pratama. The method used in this research is quantitative method. The population in this study amounted to 150 people. The sample collection technique in this study used Accidental sampling. The sample in this study amounted to 109 respondents obtained from calculations using the slovin formula. This study uses multiple linear regression analysis, and hypothesis testing using the t test and F test. The results of this study indicate that in the partial test (t) the work stress variable partially affects employee performance at PT. Sinwa Makmur Perkasa Pratama with a calculated t value of 2.093> t table 1.662 and sig value. 0.039 <0.05, job satisfaction variables partially affect employee performance at PT. Sinwa Makmur Perkasa Pratama with a t value of 7.179> t table 1.662 and sig value. 0.000 <0.05, and the results of the simultaneous test (F) the variables of job stress and job satisfaction simultaneously affect employee performance at PT. Sinwa Makmur Perkasa Pratama with the value of F count 29.358> F table 3.08 and sig value. 0,000 < 0,05.